2016
DOI: 10.1111/ijfs.13271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different treatments on the microstructure and functional and pasting properties of pigeon pea (Cajanus cajan L.), dolichos bean (Dolichos lablab L.) and jack bean (Canavalia ensiformis) flours from the north‐east Argentina

Abstract: The effect of germination (G; 5 days), soaking-cooking (SC; 6 h-20 min, 6 h-40 min, 6 h-60 min) and microwave (M; 50%, 70%, 100%) treatments on pigeon pea (PP), dolichos bean (DB) and jack bean (JB) seeds was studied. Microstructure of seeds and functional (protein solubility, water-holding capacity, oilholding capacity, emulsion stability) and pasting properties of flours were determined. Germination and microwave treatments modified the protein matrix of cotyledon cells preserving the shape of the starch gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…The granular structures were possibly starch granules, whereas smaller spheres likely represented protein bodies. The occurrence of starch granules of 7–37 μm together with relatively small spherical protein bodies of 2–4 μm has been reported for different pulses ( Acevedo et al, 2017 ; Ma et al, 2017 ; Shevkani et al, 2021b ). In general, the granules were intact and embedded partly or completely within protein matrix and surrounded with small particles which were spherical to irregular in shape.…”
Section: Resultsmentioning
confidence: 92%
“…The granular structures were possibly starch granules, whereas smaller spheres likely represented protein bodies. The occurrence of starch granules of 7–37 μm together with relatively small spherical protein bodies of 2–4 μm has been reported for different pulses ( Acevedo et al, 2017 ; Ma et al, 2017 ; Shevkani et al, 2021b ). In general, the granules were intact and embedded partly or completely within protein matrix and surrounded with small particles which were spherical to irregular in shape.…”
Section: Resultsmentioning
confidence: 92%
“…Influence of germination, soaking-cooking, and microwave treatments on pasting properties of pigeon pea, dolichos bean, and jack bean flours reduced the process of retrogradation (Acevedo et al, 2017).…”
Section: Rotational Viscometric Measurement Of Gelatinization Of Navymentioning
confidence: 99%
“…This may be due to the fact that the enzymes had hydrolyzed a significant amount of amylose and amylopectin, which resulted in the beginning of a damaged network starch. This also could lead to an increase in the starch digestibility [50]. Studies have shown that germination improves the water absorption capacity of lentil flour, namely the flour ability to absorb water, after 2-4 days of germination.…”
Section: Nutritional Characteristicsmentioning
confidence: 99%